Real-Time, Label-Free, All-Electrical Detection of Salmonella typhimurium Using Lead Zirconate Titanate/Gold-Coated Glass Cantilevers at any Relative Humidity - Zhu, Qing (2007)
We have examined non-insulated PZT/gold-coated glass cantilevers for real-time, label-free detection of Salmonella t. by partial dipping at any relative humidity. The PZT/gold-coated glass cantilevers were consisted of a 0.127 mm thick PZT layer about 0.8 mm long, 2 mm wide bonded to a 0.15 mm thick gold-coated glass layer with a 3.0 mm long gold-coated glass tip for detection. We showed that by placing the water level at the nodal point, about 0.8 mm from the free end of the gold-glass tip, there was a 1-hr window in which the resonance frequency was stable despite the water level change by evaporation at 20% relative humidity or higher. By dipping the cantilevers to their nodal point, we were able to do real-time, label-free detection without background resonance frequency corrections at any relative humidity. The partially dipped PZT/gold-coated glass cantilever exhibited mass detection sensitivity, Δm/Δf = −5×10(−11)g/Hz, and a detection concentration sensitivity, 5×10(3) cells/ml in 2 ml of liquid, which was about two orders of magnitude lower than that of a 5 MHz QCM. It was also about two orders of magnitude lower than the infection dosage and one order of magnitude lower that the detection limit of a commercial Raptor sensor.